Association of heart failure readmission with results of lung ultrasound at discharge and follow-up. (14th October 2021) - Zisis, G; Yang, Y; Whitmore, K; Lay, M; Huynh, Q; Neil, C; Carrington, M; Marwick, T H
Abstract: Background: Attainment of euvolemia at discharge and maintaining it after discharge are fundamental to avoiding readmission in heart failure (HF). Lung ultrasound (LUS) is potentially of value to detect congestion but the role of sequential LUS is undefined. Purpose: To determine the predictive value of discharge and follow-up LUS. Methods: 98 pts (mean age 72.8±12.3, mean ejection fraction 41.4%±18.4, gender male 56%) admitted with HF or fluid overload, underwent pre-discharge LUS to evaluate pulmonary (presence of ≥10 B lines) and peripheral (IVC diameter) congestion. LUS was repeated at home follow-up visits at 2 weeks post-discharge. Associations were sought between pre-discharge and follow-up LUS and 90 day outcomes (readmission or mortality). Results: Overall, there was an increase in the total number of B-lines from baseline to week 2 [mean change in B-lines 3.82 [95% confidence intervals (CI), 0.30, 7.33) p=0.036] followed by a small decrease between scan 2 and scan 3 [mean change in B-lines −0.25 (95% CI, −0.17, 7.68), p=0.94]. Of 73 with <10 B-lines pre-discharge, 26 (36%) had events by 90 days, compared with 14 of the 25 with ≥10 pre-discharge B-lines (56%, p=0.07). However, all of those with ≥10 B lines at 2 weeks had events, compared with 25% of those with <10 B lines (p=0.04). Conclusions: Attainment and preservation of euvolemia after index hospitalization for HF is challenging and requires appropriate patient support. Detection of residual congestion, as well as detection of early re-congestion after hospital discharge. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The University of MelbourneBaker Heart & Diabetes Institute